Comorbidity of Psychopathological Domains in Community-Dwelling Persons With Alzheimer’s Disease - Tractenberg, Rochelle E. (J Geriatr Psychiatry Neurol, 2003)
In this post hoc analysis of baseline responses to the CERAD Behavior Rating Scale for Dementia in a clinical trial of interventions for agitation in Alzheimer’s disease (AD), the authors investigated the distribution of, and relationships between, agitation, depression, and psychosis in 148 individuals with AD. Prevalence of depressive symptoms was highest (78.4%), followed by agitation (77.6%) and psychotic symptoms (69.3%); 51.1% of the sample had symptoms in all 3 domains. Cross-sectionally, psychotic symptoms were most closely associated with Mini-Mental State Examination (MMSE) scores, while agitation was less so. Depressive symptoms were relatively consistently prevalent across MMSE levels. After controlling for the presence of agitated symptoms, psychosis and depression were significantly associated, but neither symptoms of psychosis nor of depression were associated with agitation when depression or psychosis, respectively, was controlled for. Significant psychopathological comorbidity should be considered in the design of clinical trials targeting particular psychopathology in this disease population.